Pemanfaatan Limbah Ikan Menjadi Tepung Silase dengan Penambahan Tepung Eceng Gondok (Eichhornia crassipes) - Zella Dwi Jayanti; Herpandi Herpandi; Shanti Dwita Lestari (Jurnal FishtecH, 2018)
The purposes of this research were to utilize fish waste and to study effect of water hyacinth flour nonfermented and fermented as material of silage . Data were analyzed using paired sample t-test trought SPSS 16.0 programme. Treatments included different fish waste raw material (fresh water and sea water) dan the type of water hyacinth (fermented and nonfermented flour) added with 3 repetation. Based on the result of t test indicate that the different type of fish waste is significantly different from the content of ash, fat content and calcium on silage flour. While differences in water hyacinth flour significantly different to the bulk density, moisture content, protein, and crude fiber in the resulting silage flour. Different types of fish waste and water hyacinth flour were not significantly different from the phosphorus content, and NaCl in the resulting silage flour. Product that approach SNI quality of fish flour is using raw material sea water fish waste with the addition of water hyacinth fermented flour which obtained 0.56% bulk density, 11.91% water content, 22.73% ash content, 46.5% protein content, 15.19% fat content, 2.34% crude fiber content, 3.1% calcium, 2.26% phosphorus, and 2.65% NaCl.